DIRECTIONS FOR IMPROVING AN ANTI-CRISIS MANAGEMENT STRATEGY IN THE ENTERPRISE (Marketing Journal, 2025)
This article analyzes the directions of improving the anti -crisis management strategy at the enterprise on a scientific basis. The study separately studied the issues of early detection of crisis situations, comprehensive assessment and monitoring of risks , increasing strategic flexibility, and ensuring financial stability. Also, the role of 427 the use of digital technologies and innovative approaches in anti -crisis management for enterprises in modern conditions was widely covered. The proposals and recommendations developed on the basis of foreign and national experience are aimed at increasing the crisis resilience of enterprises and expanding their opportunities for ensuring their strategic sustainable development.
Keywords: anti-crisis strategy; risk management; strategic flexibility; financial stability; innovative approaches; digital transformation; enterprise management